Ballasted sand flocculation for water, wastewater and CSO treatment. Issue 1 (1st January 2016) - Kumar, Sumant; Ghosh, Narayan C.; Kazmi, A. A.
Abstract : Ballasted Sand Flocculation (BSF) technique based on coagulation and flocculation with injection of micro-sand has emerged as an efficient and quick method for treatment of water, wastewater and combined sewer overflow (CSO). Micro-sand as ballast agent increases both settling velocity and overflow rate that reduces the system's land footprints compared to the conventional coagulation/flocculation/clarification processes. Different types of coagulants, flocculants and micro-sand of varying dosages, depend on influent hydraulic loadings and their water-quality constituents' characteristics, are used in BSF. The coagulant dosages of alum and ferric chloride normally vary from 8 to 40 mg/l and 40 to 190 mg/l, respectively; the flocculent dosages (cationic/anionic polymer) vary from 0.3 to1 mg/l, and the micro-sand (size 40–150 µm) dosages from 2 to 12 g/l based on type and characteristic of water/wastewater. In most of the cases, the removal rate of turbidity, TSS and T-P were reported above 90% and BOD above 60%. The removal rate of other parameters (viz. coliforms, COD and trace elements) was also reported satisfactory. BSF system has been found a promising technology for clarification of drinking water and in reducing pollution load of wastewater and CSO treatment system before its pathways to biological processes, or natural water systems. The article presents a review and critical appraisal of BSF technology on its processes, chemical and sand dosages, performance, usefulness and drawbacks.